ASSESSING THE IMPACT OF STEM EDUCATION ON STUDENTS' ACADEMIC PERFORMANCE IN SOLAR ENERGY STUDIES - Ramankulov, Ш.; Zhaksylyk, Н.; Kurbanbekov, Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
Integrating STEM (Science, Technology, Engineering, and Mathematics) Education into Solar Energy Curricula as a Key Strategy for Enhancing Students' Interaction and Understanding of Solar Energy Technologies. STEM education can be considered a key strategy for integrating solar energy studies into academic curricula to enhance students' interaction and comprehension of solar energy technologies. This approach not only fosters critical thinking and problem-solving skills but also prepares students for future careers in sustainable energy. The objective of this study is to evaluate the effectiveness of implementing STEM methods in solar energy education. The efficiency of STEM education in solar energy can be assessed through various criteria, including curriculum development, pedagogical strategies, and environmental awareness. As part of this study, scientific research related to this topic and STEM projects based on alternative energy sources were analyzed. A pedagogical experiment was conducted within the physics education curriculum for the course "Alternative Energy Sources." A total of 51 students participated in the experiment. The learning process utilized an educational-scientific stand designed to study the physical characteristics of solar energy converters, Vernier sensors for data collection, and the Vernier Graphical Analysis program to analyze the relationship between solar panel performance and light intensity. Quantitative data were analyzed using mathematical-statistical methods in the JASP software to observe the correlation between the frequency of STEM product usage and exam scores. The Pearson correlation coefficient was found to be r = 0.575, indicating a positive correlation, with p < 0.001, confirming statistical significance. Linear regression analysis yielded a value of R² = 0.331, suggesting that the use of STEM products explains approximately 33% of the variation in exam scores. The study results confirm that the use of STEM-based educational tools focused on solar energy positively impacts students' academic performance. The findings highlight the significance of incorporating STEM approaches into solar energy education programs, contributing to the training of highly qualified specialists in the field of renewable energy. This research can serve as a foundation for the implementation of innovative technologies in the education system.